Biografi Tokoh Tasawuf Al-Ghazali - Lidia Artika; M Yaffi Rabbani; Muhammad Ridho Rizky Nafis; Nursyahri Siregar; Indra Gusnanda (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2023)
The purpose of this research is to find out the Biography of the Sufism Figure Al-Ghazali. This research uses a biographical research method, which is a method of analyzing a person's life history. The object of study is the person and his entire life experience. Starting from his birth, becoming an adult, up to his old age, even until the person dies.... The conclusion in this study is to combine fiqh and Sufism al-Ghazali uses two methods, namely internal and external methods. What is meant by the internal method is the way al-Ghazali sees the internal aspects of fiqh and Sufism. Maskawaih argues that everything that exists grows and develops through several phases, all of which are the chain of life. That in the first phase is something simple, then always evolving and developing so that it reaches a higher degree.